2015
DOI: 10.1371/journal.pone.0128641
|View full text |Cite
|
Sign up to set email alerts
|

Delay and Probability Discounting of Sexual and Monetary Outcomes in Individuals with Cocaine Use Disorders and Matched Controls

Abstract: Individuals with cocaine use disorders are disproportionately affected by HIV/AIDS, partly due to higher rates of unprotected sex. Recent research suggests delay discounting of condom use is a factor in sexual HIV risk. Delay discounting is a behavioral economic concept describing how delaying an event reduces that event’s value or impact on behavior. Probability discounting is a related concept describing how the uncertainty of an event decreases its impact on behavior. Individuals with cocaine use disorders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
93
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 81 publications
10
93
0
Order By: Relevance
“…The current study extends earlier research examining delay discounting of condom-protected sex with samples at high-risk for STI contraction and transmission, including individuals with substance use disorders (e.g., Herrmann et al, 2014; Herrmann et al, 2015; Johnson & Bruner, 2012; Johnson et al, 2015) and youth from socioeconomically disadvantaged backgrounds (Dariotis & Johnson, 2015). The present study demonstrates that college students are less likely to use an immediately available condom and less likely to wait to engage in condom-protected sex when partners are viewed as more desirable (i.e., MOST WANT SEX) and less likely to have an STI (i.e., LEAST LIKELY STI).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The current study extends earlier research examining delay discounting of condom-protected sex with samples at high-risk for STI contraction and transmission, including individuals with substance use disorders (e.g., Herrmann et al, 2014; Herrmann et al, 2015; Johnson & Bruner, 2012; Johnson et al, 2015) and youth from socioeconomically disadvantaged backgrounds (Dariotis & Johnson, 2015). The present study demonstrates that college students are less likely to use an immediately available condom and less likely to wait to engage in condom-protected sex when partners are viewed as more desirable (i.e., MOST WANT SEX) and less likely to have an STI (i.e., LEAST LIKELY STI).…”
Section: Discussionsupporting
confidence: 72%
“…The SDDT has shown associations with self-reported risky sex behaviors and high test-retest reliability (Johnson & Bruner, 2012; 2013; Herrmann et al, 2015), and multiple studies have found that users of illicit substances discount condom-protected sex more steeply than healthy controls (Bruner & Johnson, 2012; Herrmann et al, 2014; Herrmann et al, 2015; Johnson, Johnson, Herrmann & Sweeney 2015). Recently, a SDDT study of youth (18–25 years old) recruited from an urban city and surrounding metro area characterized by high STI prevalence rates, crime, and drug use (Dariotis & Johnson, 2015) indicated greater sexual delay discounting for hypothetical partners that they judged as “most want to have sex with” (relative to “least”) and “least likely to have an STI” (relative to “most”), with males showing higher likelihood of engaging in unprotected sex than females when facing no delay but no sex differences in the rate of sexual delay discounting.…”
mentioning
confidence: 99%
“…In particular, cocaine-dependent methadone patients who had alcohol use disorders were more likely than those without alcohol use disorders to engage in some of the highest risk HIV sexual risk behaviors (i.e., transactional and anal sex). These results are consistent with findings from previous studies which have shown cocaine-dependence is associated with risky sexual decision-making (Johnson, Johnson, Herrmann, & Sweeney, 2015), and alcohol use increases individuals’ intentions to engage in risky sexual behavior (Johnson et al, 2016; Rehm et al, 2012). …”
Section: Discussionsupporting
confidence: 92%
“…29,[31][32][33] As with monetary delay discounting, individuals with a history of risk behavior (e.g., substance abuse) show steeper delay discounting of condom-protected sex. [31][32][33][34] Collectively, studies that examined monetary and sexual delay discounting outcomes suggest that delay discounting is a fundamental behavioral process related to risk behavior. To our knowledge, however, no studies have investigated the relationship between energy drink use and monetary or sexual delay discounting.…”
Section: Introductionmentioning
confidence: 99%